The Effect of Personality on Work-Related Fatigue Through Emotional Intelligence Among Employees of the Regional Secretariat of Cirebon Regency - Imel Alghi Dwiagistri; Kartono Kartono (Publikasi Indonesia, 2026)
This study aims to examine the effect of personality on work-related fatigue through emotional intelligence as a mediating variable among employees of the Regional Secretariat of Cirebon Regency. The research employed a quantitative approach using an explanatory survey method with a sample of 80 employees selected through proportionate stratified random sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression and mediation analysis with the Baron and Kenny approach, supported by the Sobel test using SPSS. The results indicated that personality has a positive and significant effect on work-related fatigue, suggesting that individual personality traits play an important role in determining fatigue levels. Personality is also found to significantly influence emotional intelligence, indicating that personality characteristics shape an individual’s ability to recognize and manage emotions. Furthermore, emotional intelligence has a significant effect on work-related fatigue, showing that higher emotional sensitivity may increase emotional burden in bureaucratic work environments. Mediation analysis reveals that emotional intelligence partially mediates the relationship between personality and work-related fatigue, meaning that personality influences fatigue both directly and indirectly through emotional intelligence. This study contributes to the development of organizational behavior theory in the public sector by integrating personality, emotional intelligence, and burnout within a single framework. Practically, the findings suggest that improving emotional intelligence through training programs can be an effective strategy to reduce work fatigue among public sector employees.